Media Pembelajaran 5m Meretas Kendala Guru Dalam Membentuk Karakter Siswa ”Thumb Generation” Berakhlak Mulia - Maria Patricia Tjasmadi (Proceedings of The ICECRS, 2018)
The general discription that comes when hearing the words of Student Thumb Generation (STG) is; technology literate student, high curiosity, multi-tasking, creative and innovative, and responsive to change. In addition to these positive things, there is a negative side that is quite apprehensive and will impact on everyday life and association. In general, STG tends to be selfish, narcissistic, and intolerant.If the above advantages can be combined with noble character, the competency standard of the graduates specified in the Regulation of the Minister of Education and Culture No. 54 of 2013 on the qualification of graduate ability that includes attitude, knowledge, and skills can be realized. Given the attitude dimension in accordance with the Minister Regulation above, the writer will explain about the utilization of 5M learning media that can motivate STG at elementary school education level to build behavior that reflect the attitude of the faithful, noble, knowledgeable, confident, and responsible in interacting effectively with the social and natural environment in the home, school, and playground. 5M learning media can be obtained easily and can be adapted to the depth of teaching materials, because in general the raw materials of this media can be obtained around the life of students. Through the empowerment of this media, STG can interact well so that noble character can be build.